Umirajoči bolnik in zdravnik družinske medicine - Mazej Poredoš, Barbara (Medicinski razgledi, 2008)
A family practitioner gets involved in a relationship with a terminally ill patient sooner or later. In that life period, his role is extremely important,since the patient and his family need a widely based approach. The first challenge for the doctor is how to tell the bad news, because every family reacts in its own manner. The next challenge is how to prepare an appropriate plan of management and treatment. Holistic, multidisciplinary based paliative care is used to alleviate annoying symptoms and difficulties, to assure proper medical care and help coping with different psychological, social and spiritual matters. There are many institutional and informal services available to provide help for the dying and his family: medical care,social care, hospices, religious organizations and other services, so thebest possible quality of life can be achieved. Most of the dying patients wish to die at home, so the family practitioner tries to establish the care atthat place as long as possible. At the time of death, the family practitioner also examines the corpse, in case that is his duty. After the patient dies, his role continues with counselling his family members during the time of mourning.
Keywords: Družinska medicina; Palliative Care; Zdravniški obiski; Family Practice; House Calls; Paliativna oskrba; Homes For The Aged; Smrt; Death; Domovi za starostnike; Hospic, oskrba; Hospice Care; umirajoči bolnik